Christian women groups contributions and community development in Opobo/Nkoro Local Government Area, Rivers State, Nigeria: Implications for social work practice (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
This paper examines the contributions of Christian women groups and community development in Opobo /Nkoro Local Government Area of Rivers State, Nigeria; and its implications and opportunities for social work practice. Literature were reviewed and the social capital theory was adopted to explain the phenomenon. The methodology use for this research was the survey research design. And the population was drawn from the entire members of the Women Groups in Opobo/Nkoro, the sample size for this study is 120 respondents randomly selected. The instrument of data collection was the questionnaire and the data collected was recorded and analysed by frequency distribution tables and the statistical package for social sciences (SPSS) version 13, data collected were subjected to chi- square statistical analysis for testing the study hypothesis. The finding reveals that most of the sources of Iincome and funding by Christian women groups in Opobo came from lunching and ceremonies, levies loans and self-help contributions and donations. It was recommended among others that women and women groups should be empowered financially and economically to enable contribute meaningfully and participate actively incommunity development projects.
Keywords: Christian Women; Groups; Contributions; Community; Development